Control Radiation Pattern for Half Width Microstrip Leaky Wave Antenna by Using PIN Diodes - Mowafak khadom Mohsen; M.S.M. Isa; Z. Zakaria; A.A.M. Isa; M. K. Abdulhameed; Mothana L. Attiah (Institute of Advanced Engineering and Science, 2018)
In this paper, a novel design for single-layer half width microstrip leakywave antenna (HW-MLWA) is demonstrated. This model can be digitally control its radiation pattern at operation frequency and uses only two values of the bias voltage, with better impedance matching and insignificant gain variation. The scanning and controlling the radiation pattern of leaky-wave antennas (LWA) in steps at an operation frequency, by using switches PIN diodes, is investigated and a novel HW-MLWA is introduced. A control cell reconfigurable, that can be switched between two states, is the basic element of the antenna. The periodic LWA is molded by identical control cells where as a control radiation pattern is developed by combining numerous reconfigurable control cells. A gap capacitor is independently connected or disconnected in every unit cell by using a PIN diode switch to achieve fixedfrequency control radiation pattern scanning. The profile reactance at the free edge of (HW-MLWA) and thus the main lobe direction is altered by changing the states of the control cell. The antenna presented in this paper, can scan main beam between 18o to 44o at fixed frequency of 4.2 GHz with measured peak gain of 12.29 dBi.